Investment Contribution in Improving Community Welfare through Employment Opportunities - Rustam, Rustam (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Labor problems are not only limited to demographic problems but problems that cover various dimensions, the extreme point is that high unemployment rates can create problems at the social and economic levels. So this research aims to examine how the role of investment contributions, economic growth, education, infrastructure, and wages in influencing community welfare through employment opportunities. This research study was conducted using a literature review approach. The results show that the variables that affect the level of community welfare through employment opportunities are investment, economic growth, education, infrastructure. Another particular thing in increasing employment opportunities is that the government has an important role in the openness of a country in order to be able to prosper its people. Meanwhile, wages have a negative relationship in influencing employment opportunities.